An Analysis of Nominalization in Kimps' Scientific Text - Nurina Rahma Zhafira; Susie Chrismalia Garnida (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
The aim of this study is to analyze the nominalizations found in the scientific text. Nominalization is a linguistic resource that enable the condensation of information by expressing events, properties, actions situations, and clause relations in an abstract or incongruent manner (Halliday, 2004: 172). There is an aspect of nominalization that must be required to find out, it is the logical structure of the noun phrase. This research used descriptive qualitative method, from journal article entitles “A Speech Function Analysis of tag Questions in British English Spontaneous Dialogue” (Kimps, Ditte; Kristin Davidse & Bert Cornillie 2014). The researcher took 30 sentences that contains a nominalization. It is found 32 nominalizations that derived from verbs as a deverbal noun and 2 nominalizations as a verbal noun. On the other hand, 7 data of adjective-noun that were the nominalization derived from adjectives.